Maximal oxygen uptake and cardiorespiratory response to maximal 400-m free swimming, running and cycling tests in competitive swimmers - Rodriguez, F. A. (The Journal of Sports Medicine and Physical Fitness, 2000)
This study compared the cardiorespiratory response of trained swimmers to 400-m unimpeded front crawl swimming (SW), treadmill running (TR) and ergometer cycling (EC) maximal exercise tests, and evaluated the validity and specificity of a method to measure maximal aerobic power in swimming. METHODS: Two series of experiments were conducted. In series A (n=15), comparisons were made between VO2peak and other cardiorespiratory variables in three maximal tests: after 400-m SW, and during incremental TR and EC. In series B, VO2 peak and related variables were measured after SW and during EC (n=33). RESULTS: No significant differences were observed between VO2peak and VE in the three modes of exercise, although SW values tended to be higher. After SW, maximal ventilatory response was characterized by higher tidal volumes (VT) and lower respiratory rates (fR) as compared with TR and EC. The highest heart rate values (fH) were also observed in TR, followed by EC and SW. In series B, no significant differences were observed either in peak VO2 or VE, but fH was also lower in SW. CONCLUSIONS: A maximal 400-m unimpeded freestyle SW test yields essentially equal or nonsignificantly higher peak VO2 and VE values than during maximal TR or EC tests in trained swimmers. The specific maximal cardiorespiratory response to the SW test is characterized by higher VT, lower fR, and lower fH. Breath-by-breath measurements during the immediate recovery after a 400-m voluntary maximal swim is proposed as a valid and specific test for directly measuring maximal metabolic parameters and evaluating specific maximal aerobic power in swimming.